2019
DOI: 10.4103/ijmbs.ijmbs_77_19
|View full text |Cite
|
Sign up to set email alerts
|

The Year in “Ramadan Fasting and Health” (2018): A Narrative Review

Abstract: Invited Review introduCtionRamadan fasting (RF) is practiced by adult Muslims during the 9 th lunar month every year. It entails that they abstain from eating and drinking between dawn and sunset. Medical and religious scholars got closer in their approach to advice given to patients based on objective risk assessment. [1] Muslim patients with acute or chronic medical conditions may be exempted from fasting; many do still choose to observe the fast sometimes against medical advice. This may adversely affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…A narrative literature review of all peer-reviewed publications looking at the health implications of Ramadan fasting was undertaken in 2018 [53]. The majority of studies reviewed suggested that under normal circumstances, Ramadan fasting was safe for persons with mild and stable medical conditions.…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…A narrative literature review of all peer-reviewed publications looking at the health implications of Ramadan fasting was undertaken in 2018 [53]. The majority of studies reviewed suggested that under normal circumstances, Ramadan fasting was safe for persons with mild and stable medical conditions.…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…The questionnaire consisted of 22 close-ended questions (Additional file 1 ) that encompassed the following determinants and was developed in compliance with the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) guidelines [ 10 , 36 ] and the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines [ 37 ]: Demographic characteristics (age, sex, residency, education, employment status, weight, height and medical diagnoses) Intermittent fasting practices (patterns of intermittent fasting, type of food) The effect of fasting on a person’s state of health (post-fasting portion sizes, weight loss, hunger, health status, physical symptoms) Fasting goals (cause and duration of the practice, plans, sources of knowledge about intermittent fasting, resources on intermittent fasting) Use of technology in fasting (name of the app if applicable) …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the majority of the research on intermittent fasting based in Muslim countries has been limited to the study of the physiological effects of fasting during Ramadan, for example, the effect of fasting during Ramadan on diabetes treatment [ 10 , 13 , 14 ], cardiovascular disease [ 1 , 15 , 16 ], body weight [ 17 – 19 ], athletic performance [ 20 – 22 ] and sleep [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies showed that Ramadan fasting resulted in significant reductions in fasting plasma glucose, HbA1c and BMI [ 72 , 73 ], other studies in the MENA region demonstrated a deterioration in glycemic control [ 74 , 75 ], which was more evident in patients on insulin or oral hypoglycemic agents [ 75 , 76 ]. Thus, it was concluded that Ramadan fasting may be deemed safe for individuals with mild and stable medical conditions however, for high-risk diabetes patients, individualized MNT is required [ 77 , 78 ].…”
Section: Dietary Management Of Diabetesmentioning
confidence: 99%